(untitled) (Research, Society and Development, 2022)
This study aimed to analyze and describe the epidemiological profile of tuberculosis cases in the state of Paraíba, in the period between 2010 and 2019. This is an epidemiological, retrospective study, with a descriptive and quantitative approach, carried out from secondary sources. A data survey was carried out in the Notifiable Diseases Information System, with analysis of the variables: year of notification, health macro-region/city of notification, gender, age group, education, clinical form, 1st and 2nd bacilloscopy, sputum culture, HIV and foreclosure status. Data were processed in Microsoft Office®, Microsoft Excel® 2016 and TabWin version 4.15. A total of 13,664 cases were registered, the largest flow was present in João Pessoa, Campina Grande and Patos. Throughout the period, there was a predominance of male individuals, aged between 20 and 59 years. As for education, there was a prevalence of incomplete 1st to 4th grade of elementary school, 2.522 (18,46%). The first sputum smear microscopy had the highest number of positive results, 7.295 cases, while culture was less performed (11.530). Greater involvement of the pulmonary form (84,13%). Positive HIV test results accounted for 1.138 cases (8,33%). Cure was prevalent in all years evaluated, corresponding to 7.879 (57,66%). Thus, despite tuberculosis being a disease with treatment and cure, the number of individuals affected by this pathology is still significant, as well as its close relationship with more precarious socioeconomic conditions and the impact of TB-HIV co-infection.